THE INFLUENCE OF AVIATION SECURITY OFFICERS (AVSEC) SERVICE QUALITY ON PASSENGER SAFETY SATISFACTION - Ibrahim, Achmad; Iswahyudi, Prasetyo; Maharani Sukma, Meita (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
The purpose of this study was to find out how much influence the quality of avsec security service has on passenger satisfaction at Sultan Thaha Jambi airport. This study uses a type of quantitative research with a questionnaire as the primary data source. The population in this study were passengers at Sultan Thaha Airport, Jambi. The samples taken were 45 passengers at Sultan Thaha Airport, Jambi. The method used in this research uses descriptive quantitative research methods with the research that has been done, it is found that the results of the F test have a significant value of 0.000 - 0.005, which means that there is an influence from the quality of security service avsec officers have on passenger satisfaction at Sultan Thaha Jambi Airport. Based on the results of the simple regression test, a result of 0.852 or equal to 85.2% was obtained. The conclusion results show that the effect of the quality of security services for Aviation Security officers (AVSEC) gets a strong correlation with the passenger satisfaction variable and the remaining 14.8% or 0.148 is a variable not examined in this study